EVALUASI PERATURAN DAERAH KABUPATEN INDRAGIRI HILIR NOMOR 21 TAHUN 2008 TENTANG KETERTIBAN UMUM (Studi di Kecamatan Tembilahan) - Susanto, Nofri; Khotami, Khotami (UIR PRESS, 2015)
Execution of By Law of Kabupaten Indragiri Hilir No 21 Tahun2008 About Common/ public Orderliness in Subdistrict Tembilahan represent one of regulation which aim to to realize freshment, save orderliness and for all citizen socialize. To know clearer hence the researcher use 6 assessment indicator that is efectivity, Efficiency, Responsivitas, Sufficiency, Accuracy And Generalization. Research Type used by is descriptive research with quantitative research method approach where writer will depict real situation whereof that happened the research location namely in Subdistrict Tembilahan. this Sample Research is used by two withdrawal sample technique that is for Sub-kabupaten Tembilahan and Lead Hygiene Area by using census technique. While to socialize Subdistrict Tembilahan specified with technique Purposive Sampling. Technique of data collecting of through kuissioner, interview and observation. Pursuant to result analyse in this research is writer conclude that Execution of By Law of kabupaten indragiri hilir no 21 tahun 2008 About Common/ public Orderliness in Subdistrict Tembilahan be at Good Enough assessment category. As for suggestion which can be passed to On Duty the Hygiene: First, Giving addition of ash can to socialize in order to can accomodate to the number of garbage volume which thrown by society. Second, correct schedule And Timing in execution program hygiene in order to the society able to participate in an optimal fashion.